Comparative Study of Recovery Time between Endoscopic and Microscopic Tympanoplasty a Randomized Controlled Trial - Dr. Sudip Kumar Nath; Dr. Nandita Nath; Dr Smrity Rupa Borah Dutta (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Background: Endoscopic tympanoplasty has emerged as a minimally invasive alternative to the traditional microscopic technique in the surgical management of chronic otitis media. While both approaches aim to restore hearing and achieve successful graft uptake, their comparative impact on recovery time remains under-investigated. Methods: This prospective randomized controlled trial was conducted at Silchar Medical College & Hospital between January 2022 and December 2024. A total of 120 patients diagnosed with chronic otitis media with tympanic membrane perforation were randomly assigned to undergo either endoscopic (n=60) or microscopic (n=60) tympanoplasty. Outcome parameters included hospital stay duration, time to return to normal activities, hearing improvement (measured by pure-tone audiometry), patient satisfaction, and complication rates. Follow-up was conducted for six months postoperatively. Results: Patients in the endoscopic group had significantly shorter mean hospital stays (1.2 ± 0.4 vs. 2.5 ± 0.6 days; p<0.001) and returned to normal activities more quickly (7.8 ± 2.1 vs. 11.3 ± 3.2 days; p<0.001). Both groups demonstrated comparable postoperative hearing improvement (mean gain: 18.8 ± 7.2 dB vs. 17.8 ± 6.9 dB; p=0.401). Patient satisfaction scores were significantly higher in the endoscopic group (p<0.001), with no notable difference in complication rates between the two techniques. Conclusion: Endoscopic tympanoplasty offers a significantly shorter recovery time and superior patient satisfaction compared to the microscopic approach, without compromising hearing outcomes or safety. These findings support its broader adoption in appropriate clinical settings.